Issues of Accountability in Cloud Computing Environment - Kanta Mohanty, Surjya; Mishra, Samaresh; Kumar Pattnaik, Prasant (International Journal of Engineering and Technology, 2018)
In an accountable Cloud Computing Environment the system able to handle Â even the smallest action being performed by any entity in the environment and trace the entity that performed such as action to hold same accountable for mishap/risk if any. It is very essential that evidence of all the activity stored and processed may be maintained and stored for recovery in the future if required. This stored/maintained data are required to have enough information so that a particular activity can be properly scrutinized. This process should be an iterative process in order to achieve excellence in the system of the Cloud. This paper addresses the issues of accountability in a cloud computing environment.Â